The genus Aurinia Desv. (Brassicaceae) in ZA and ZAHO herbaria - Rešetnik, Ivana (Array, 2020)
This paper presents the collection of the genus Aurinia Desv. species in ZA and ZAHO herbaria. The revision and the analyses of the material are presented. Herbarium specimens from these two herbaria were digitized and the data from the original herbarium labels were inserted in the Flora Croatica Database. A total of 203 herbarium sheets were digitized and nine taxa (A. corymbosa Griesb., A. leucadea (Guss.) K. Koch ssp. leucadea, A. leucadea (Guss.) K. Koch ssp. media (Host) Plazibat, A. petraea (Ard.) Schur, A. petraea (Ard.) Schur ssp. microcarpa (Vis.) Plazibat, A. saxatilis (L.) Desv., A. saxatilis (L.) Desv. ssp. orientalis (Ard.) T. R. Dudley, A. saxatilis (L.) Desv. ssp. saxatilis, A. sinuata (L.) Griseb.) were registered within studied collections. The specimens originate from 16 European countries and the majority of herbarium sheets were collected in Croatia. The majority of specimens were collected between 1900s and 1950s. The comparison between the recorded distribution data in the Flora Croatica Database and the distribution based on herbarium specimens is made and the herbarium specimens generally well represent the distribution range of studied taxa.